Oral 4-aminosalicylic acid versus 5-aminosalicylic acid slow release tablets. Double blind, controlled pilot study in the maintenance treatment of Crohn's ileocolitis. Issue 8 (August 1994) - Schreiber, S; Howaldt, S; Raedler, A
Abstract : 4-Aminosalicylic acid (4-ASA) has been suggested as an effective treatment for both active and quiescent ulcerative colitis. 5-Aminosalicylic acid (5-ASA) is well accepted for the maintenance treatment of inactive ulcerative colitis. Moreover, recent studies suggest that 5-ASA may also be effective in maintaining remission in Crohn's colitis. As treatment with 4-ASA may result in less side effects, the efficacy of a one year's maintenance treatment with oral 4-ASA (1.5 g/d, slow release tablets, n = 19) and oral 5-ASA (1.5 g/d, slow release tablets, n = 21) was compared in a double blind, randomised trial in patients with quiescent Crohn's ileocolitis. Patients with ileocolonic or colonic involvement were enrolled if in stable remission for more than two months but less than one year. Baseline demography and clinical severity were similar in both groups. Total colonoscopy and ileoscopy were performed at enrollment and at the end of the study. After one year seven of 19 patients receiving 4-ASA (36%) and 8 of 21 receiving 5-ASA (38%) had developed a clinical relapse, as defined by a rise in the Crohn's disease activity index (CDAI) of more than 100 points to values higher than 150. The relapse rates between the 4-ASA and the 5-ASA groups were not statistically different although no comparison with the spontaneous relapse rate in a placebo group could be made. Clinical relapse was accompanied by a statistically significant rise in serum concentrations of soluble interleukin 2 receptor and by an increased percentage of activated peripheral blood T cells. There were no statistical differences between the 4-ASA and the 5-ASA groups regarding the height of rise in CDAI or of soluble interleukin 2 receptor concentrations during relapse, thus showing a similar severity relapsed disease activity. In conclusion, 4-ASA maybe as effective as 5-ASA in the maintenance treatment of quiescent Crohn's disease and there were no differences in the severity of relapse between both treatment groups.